TANTANGAN KESEJAHTERAAN SUBJEKTIF PELAJAR DALAM TRANSISI KURIKULUM MERDEKA: STUDI KASUS DI SMAS MAITREYAWIRA BATAM - Marcellio Antoni Tan; Martinus Danang Pamungkas (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2026)
In recent decades, the issue of quality of life has become a concern in many fields of study, one of which is education. Therefore, education is considered one of the factors that drive subjective well-being in educational institutions. This study aims to analyze the challenges of subjective well-being of students at Maitreyawira Batam High School in learning the independent curriculum and to analyze the subjective well-being of students. Using qualitative research methods, data were collected through observation, interviews, and documentation from 11 research informants. The researcher then analyzed the data using data condensation, data presentation, and conclusion drawing. The results of this study indicate that the national curriculum still has obstacles to subjective well-being, with the existence of several negative affects. However, behind the shortcomings of the national curriculum, there is a good cognitive assessment that the national curriculum can support students in improving their quality of life in achieving their goals and aspirations. The results of this study offer a contribution in the form of new ideas in analyzing the education curriculum as a driver of the phenomenon of quality of life.